2016
DOI: 10.1017/s1047951116002109
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, suicidal ideation, and stressful life events in non-cardiac adolescent chest pain: a comparative study about the hidden part of the iceberg

Abstract: Chest pain in adolescents is rarely associated with cardiac disease. Adolescents with medically unexplained chest pain usually have high levels of anxiety and depression. Psychological stress may trigger non-cardiac chest pain. This study evaluated risk factors that particularly characterise adolescence, such as major stressful events, in a clinical population. The present study was conducted on 100 adolescents with non-cardiac chest pain and 76 control subjects. Stressful life events were assessed by intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
1
17
0
2
Order By: Relevance
“…The majority of selected studies had been published in the last decade (n=20 33,34,36,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] ; 80% published after 2010; table 1). Studies were geographically diverse, and mainly based on community samples (n=17 [33][34][35][36]43,44,[46][47][48][49][50][51]53,55,[57][58][59] ), using cross-sectional designs (n=18 35,41,43,46,47,[49][50][51][52][53][54][55][56]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of selected studies had been published in the last decade (n=20 33,34,36,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] ; 80% published after 2010; table 1). Studies were geographically diverse, and mainly based on community samples (n=17 [33][34][35][36]43,44,[46][47][48][49][50][51]53,55,[57][58][59] ), using cross-sectional designs (n=18 35,41,43,46,47,[49][50][51][52][53][54][55][56]…”
Section: Resultsmentioning
confidence: 99%
“…Studies were geographically diverse, and mainly based on community samples (n=17 [33][34][35][36]43,44,[46][47][48][49][50][51]53,55,[57][58][59] ), using cross-sectional designs (n=18 35,41,43,46,47,[49][50][51][52][53][54][55][56][57][58][59][60][61] ). Eighteen studies recruited participants aged 10 to 19 years, [33][34][35][36]42,[45][46][47][48][50][51][52][53][57][58][59]…”
Section: Resultsmentioning
confidence: 99%
“…Several authors reported higher rates of psychogenic causes than organic causes as the aetiology of chest pain in children. 27 Khairandish 12 analysed the patients aged 11-18 years and found the psychological causes to be the second most common cause for chest pain. In McDonnell's review, 28 it has been reported that 2-19% of chest pain cases were categorised as psychological.…”
Section: Discussionmentioning
confidence: 99%
“…[19]. In another study, 100 adolescent patients with non-cardiac chest pain were compared with the control group and anxiety, depression and suicidal ideation were significantly higher in the patient group [20]. In another study investigating anxiety, depression, and attention deficit and hyperactivity disorder in patients with non-cardiac chest pain, anxiety was found at a rate of 76% and depression at 24% [21].…”
Section: Discussionmentioning
confidence: 98%